[OP.5C.04] HEART RATE IS ASSOCIATED WITH GLOMERULAR HYPERFILTRATION IN APPARENTLY HEALTHY SUBJECTS. (September 2016) - Vrdoljak, A.; Ivkovic, V.; Karanovic, S.; Dika, Z.; Domislovic, V.; Dapic, K.; Gallineo, L.; Ivandic, E.; Josipovic, J.; Vukovic, I.; Kos, J.; Laganovic, M.; et al.
Abstract : Objective: Glomerular hyperfiltration (GHF) was associated with progression of kidney disease and hypertension (HT). It was reported that high metabolic risk is related to increase of GHF. Our aim was to analyze in apparently healthy subjects which factor(s) influence (s) GHF and determine(s) clinical course in long-term prospective study. Design and method: Out of 954 subjects enrolled in ENAH follow-up study, 371 (137 m, 234w; mean age = 46years) were eligible for further analysis:100 with optimal, 72 with normal BP, 70 with PHT (high normal BP), and 129 with newly diagnosed untreated HT. Follow-up period was 77 ± 12 months. Exclusion criteria were treatment with antihypertensive drugs, diabetes, pregnancy, eGFR < 60 ml/min, CV or cerebrovascular incident, chronic terminal diseases, dementia, immobility and missing data. BP and heart rate were measured using Omron 6 device following the ESH guidelines. Uric acid, glucose, lipids, serum creatinine, hsCRP, leptin and adiponectin were determined; HOMA index was used to calculate insulin resistance and MDRD formula to estimate GFR. Albumin to creatinine ratio (ACR) was determined from the first morning spot urine. GHF was defined as eGFR above the cut off value of the 5th quintile of the whole group. Results: Subjects with GHF were younger (38.1 vs. 48 13), had smaller waist circumfernce (87 ± 17 vs. 92 ± 16), lower BP (121/76 vs. 131/81), total cholesterol (5.3 ± 1.1 vs. 5.8 ± 1.1) LDL-cholesterol (3.1 ± 0.9 vs. 3.5 ± 1.0) and leptin (C 5, 1 (IQ2.8–10.7) vs. 10.4 (5.4–16.6) compared to others; all p < 0.05. Neither metabolic factors nor BP values were assosiated with GHF. However, GHF was positively associated with HR in a way that every 1 beat/min increases odds for hyperfiltration for 7% (1.07 [1.02, 1.13]) at baseline for 6% at the end of follow up (1.06 [1.01, 1.10]). Conclusions: Contrary to some reports from literature, our group of apparently healthy subjects with GHF did not have increased metabolic risk. Interestingly, according to our results heart rate is positively associated with GFH indicating that increased sympathetic activity might have important role.